Effects of Carvedilol on Isolated Heart Mitochondria: Evidence for a Protonophoretic Mechanism - Oliveira, Paulo J. (2000)
Carvedilol ({1-[carbazolyl-(4)-oxy]-3-[2-methoxyphenoxyethyl)amino]-propanol-(2)}) is a novel compound used in clinical practice for the treatment of congestive heart failure, mild to moderate hypertension, and myocardial infarction. Carvedilol was also shown to protect cardiac mitochondria from oxidative stress events. Because mitochondria are the main suppliers of ATP for cardiac muscle work, a study of the effects of carvedilol in mitochondrial bioenergetics is necessary to fully understand the basis of its protective role in myocardial energetics. In this work we show that carvedilol acts as an uncoupler of oxidative phosphorylation, decreasing mitochondrial electric potential ([Delta][Psi]) by a weak protonophoretic mechanism. Theoretical studies were carried out to determine the relevance of conformation and proton affinity of the protonable amino side-chain group in the proton-shuttling activity across the inner mitochondrial membrane. BM910228, a hydroxylated metabolite of carvedilol, was also studied for comparison with the parent compound. Implications for the protective role of carvedilol in heart mitochondrial bioenergetics are discussed.